Recent forest and land-use policy changes in Sabah, Malaysian Borneo: Are they truly transformational? - Ng, J.S.C.; Chervier, C.; Ancrenaz, M.; Naito, D.; Karsenty, A. (Elsevier, 2022)
This paper analyses the policy changes occurring in the forest and palm oil sectors of Sabah, Malaysian Borneo, through the lens of the transformational change concept. The aim is to first examine whether Sabah is transforming and, if so, to identify the determinants enabling or hindering the change. To determine if Sabah is transforming, we used two criteria: - (i) an ambitious change in the policy framework, that promotes forest conservation and sustainable use, and is moving away from business-as-usual activities; and (ii) the level of implementation of the policies that we identified as supporting transformational change. We found that Sabah very likely did intend to transform. We made this conclusion based on comparing changes in policies occurring in Sabah, and we decided if it is ambitious by primarily comparing Sabah’s policies with other Malaysian states, the federal government, and internationally. We showed that: (i) Sabah decided to use voluntary international certification standards (private market instruments) like FSC and RSPO, while the other Malaysian states did not; (ii) they decided to protect more forest compared to national and international targets; and (iii) Sabah is an early mover as the state is one of the first in the world to adopt the RSPO Jurisdictional Approach. But intention needs to be followed by implementation, and this is where the state falls short. The policies in Sabah were not fully implemented because of the patronage system where the more powerful actors used their power to continue with business-as-usual activities, there is frequent political turnover in Sabah, and the state faced difficulty in meeting international standards. Our research shows that local leadership and a local transformational change coalition (civil society actively working in Sabah) mainly prompted the transformational change, although the promises of economic gains and better reputation also played a role. We conclude by emphasising the change must be made more compelling for political leaders, as part of a broader institutional structure, not only through the narrow focus on reducing deforestation but through the development of a more sustainable and equitable national economy, and that consumer countries should play a role in reducing pressures on forest by providing incentives to a state that manages its natural resources sustainably.